PEMBERDAYAAN KEMAMPUAN UMKM DALAM BERADAPTASI DENGAN PERKEMBANGAN INDUSTRI 4.0 DI DESA JAYAGIRI KECAMATAN LEMBANG - Agus Kusmana; Syarif Ali; Iwan Kresna Setiadi; Sumilir Sumilir (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Residents in Jayagiri Village, Lembang District, West Bandung work as laborers, entrepreneurs, hotel employees and civil servants. The potential commodity in this area is tourism potential. So that marketing can be done quickly, whether they like it or not, MSMEs must even use internet-based technology to market their products. Based on this reality, efforts to overcome problems in this business for MSME players, the next stage is to prepare so that MSME players can be independent and can create digital marketing. This is done by providing training and guidance on creating digital marketing including, (1) providing an understanding of creating targeted digital marketing; (2) partners are able to create good digital marketing; (3) Creating a productive society and having additional income to support the family economy. The methods used in digital marketing training are (1) counseling/socialization; (2) training in making business plans; (3) monitoring and mentoring